Towards the Albino Mutant Gene in Malus × Domestica Borkh. - Guodong Zhao; Yang Li; Linguang Jia; Dongmei Chen; Chaohong Zhang; Xinsheng Zhang; Fengqiu Yang; Tongsheng Zhao (Plants)
Albino mutation is among the most common phenomena that often causes a water imbalance and disturbs physiological functions in higher species of trees. Albinism frequently occurs in hybridized apples, but almost all seedlings die shortly after germination. In this study, a spontaneous albino mutant on Fuji apple trees was obtained. After bud grafting, new albino shoots with greenish-white leaves grew, although they were slender, small, and died easily. Resequencing analysis indicated that a total of 49.37 Gbp clean data of the albino mutant samples was obtained; its Q30 reached 91.43%, the average rate mapped was 93.69%, and genome coverage was 96.47% (at least one base cover). Comparisons of the sequences for the albino mutants revealed 4,817,412 single-nucleotide polymorphisms (SNPs), 721,688 insertion/deletion markers (InDels), and 43,072 structural variations (SVs). The genes with non-synonymous SNPs, InDels, and SVs in CDS were compared with KEGG, GO, COG, NR, and SwissProt databases, and a total of 5700 variant genes were identified. A total of 1377 mutant genes had the GO annotation information. Among these, 1520 mutant genes had the pathway annotation and took part in 123 pathways. A total of 1935 variant genes were functionally classified into 25 COG categories. Further research on these variants could help understand the molecular regulatory mechanism of the apple albino mutant. Similarly, variations in the homologous MdAPG1 (Albino or pale-green mutant 1) gene, which was located on Chromosome 11 and belonged to the S-adenosyl-L-methionine-dependent methyltransferases superfamily, may have led to the generation of this apple albino mutant.